Pemahaman Etika Berdagang Pada Pedagang Muslim Pasar Wonokromo Surabaya (Studi Kasus Pedagang Buah) - Azizaturrohmah, Siti Nur; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Trading is a job that is highly recommended in Islam, because the Prophet and the companions also a traders. So it should as a good Muslim in performing daily activities in accordance with the guidance of the Prophet in order to be successful the world and the hereafter included in trade. Ethics of trade was good manners and behavior in the trade so the customers were satisfied.This study aims to determine the understanding of ethical trade in the Muslim traders Wonokromo Market Surabaya. This study used a qualitative approach with descriptive case study method. Determination of informants using purposive sampling technique. Data collected by means of semi-structured interviews and documentation. Data analysis using descriptive analytical model.The results of this study indicate that generally Muslim traders Wonokromo Markets have understood the ethical trade based on the principle of unity, equilibrium, free will, responsibility and truth in a way that is honest and good trade (do not cheat), provide information to the customer in accordance with reality, appropriately weigh, not hold a fake offers, do not tucking rotten fruit into a nice fruit, and helping others among fellow traders nor traders with collector.